The place of language learning in a liberal education: implications for curriculum policy in Ireland. Issue 2 (3rd April 2019) - Williams, Kevin
Abstract : This article attempts to expand, and to add to, one important aspect of the rationale for including the study of languages as part of a liberal education. Following criticism of the profile of the vocational rationale for language learning in Irish curriculum policy, the article develops recent research on the work of L. V. Shcherba to defend the role of language learning as part of a liberal education. The principal argument advanced and illustrated is that language learning has the potential to increase intellectual resources and, secondarily, to enhance literacy. This it achieves by introducing learners to new worlds of thought through revealing different linguistic maps for representing the world and by making them are aware of the nature of language. The argument is supplemented by reference to research in neuroscience that shows that knowledge of languages contributes to cognitive empowerment.